Social factors associated with practice of self-monitoring of blood glucose among type-2 diabetic patients - B. M., Sindhu; B. M., Rashmi; G., Prashanth; Kumbar, Abhinandan S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Self-monitoring of blood glucose (SMBG) is an effective self-management tool to achieve desirable haemoglobin A1c (HbA1c) targets and minimizing glucose variability, when the data is timely reviewed and acted upon by healthcare providers and diabetic patients to actively modify behaviour and/or adjust treatment. SMBG improves patient’s disease awareness and participation in disease management. Methods: This cross-sectional study was conducted at Basaveshwara Hospital, Chitradurga, to estimate percentage of type-2 diabetics practicing SMBG and to assess social factors associated with SMBG practice. Diabetic patients in age-group of 18-75 years were included in the study. Information was collected by interview technique, clinical examination and review of laboratory reports. Results: A 21.5% patients were practicing SMBG. SMBG practice was significantly higher among patients who were urban-area residents (25.0%), with higher educational qualifications (42.2% of patients who studied up-to 12th standard and/or above), with better awareness of diabetes self-management (28.9%) and with better socio-economic status (35.3%). Majority of patients with longer duration of diabetes (4.9±1.5 years), relatively older age group (57.3±2.5 years), with associated co-morbid conditions (26.8%) were found to be practicing SMBG. HbA1c levels were significantly lower among SMBG practicing group (6.6±0.7%). Conclusions: Better health literacy, higher educational qualifications, financial stability, easier access to specialized anti-diabetic health-care are favourable factors for SMBG practice. Study also highlighted favourable effect of SMBG practice on effective achievement of target HbA1c levels.